Competences in the classroom in the perspectives of foreign language teachers - Consolo, Douglas Altamiro [UNESP]; Porto, Cristina Francisca de Carvalho (My University, 2013)
In this article we raise some considerations about teachers’ competences, from the perspective of teachers in the Brazilian public sector. The theoretical framework includes articles by Paulo Freire (2001), Philippe Perrenoud (2012), Edgar Morin (2003) and Maurice Tardif (2002) and, based on these authors, we reflect upon issues concerning teachers’ competences taking answers provided by the Brazilian language teachers as a departing point. In a teachers’ course, followed by the same teachers, we posed the main question in our study: Which competences are necessary for a teacher to be considered a good professional at present? From the answers given individually and group discussions we proceeded to a comparative analysis with the adopted framework, and other issues concerning teachers’ competences were considered as well. All the participants mentioned the same two competences, the use of technology and sound knowledge of the course content, and other competences were pointed out by the various teachers as well. Such procedure, besides providing data for our study, also helped as a self-reflexive activity for the teachers involved, about their own professional performance. Given the issues raised in the theoretical texts and the answers provided by the teachers, we expect to revisit the competences necessary for foreign language teacher efficient performance.

O presente artigo tem como objetivo tecer algumas considerações acerca das competências docentes sob a perspectiva de um grupo de professores de línguas da rede pública. Adotamos como principal base teórica os textos de Paulo Freire (2001), Philippe Perrenoud (2002), Edgar Morin (2003) e Maurice Tardif (2002), e a partir destes textos fazemos algumas reflexões tomando como ponto de partida questões respondidas por professores de línguas. Durante um curso de extensão oferecido aos professores, lançamos a questão-base do nosso estudo: quais competências são necessárias para que um professor seja considerado um bom profissional na atualidade? A partir das respostas dadas individualmente e de discussões em grupo, realizamos uma análise comparativa em relação à teoria adotada, além de outros questionamentos acerca da formação dos professores. Todos os participantes apontaram as mesmas duas competências: o uso de novas tecnologias e o domínio do conteúdo ensinado. Outras competências também foram mencionadas pelos diferentes professores. Tal exercício, além de fornecer subsídios para nosso estudo, também serviu como uma autoavaliação, um exercício reflexivo dos professores em relação à própria atuação. Esperamos, a partir dos questionamentos elencados nos textos e das respostas dos professores, revisitar as competências necessárias para se atuar com eficácia no ofício de professor de línguas estrangeiras.
Competências docentes na perspectiva dos professores de línguas estrangeiras
Teachers' competences from foreign language teachers' perspectives
Keywords: Competência docente; Formação de professores|\Prática reflexiva; Ensino de línguas; Teachers’ competences; Teacher education; Reflexive practice; Language teaching